Effectiveness of competency-based training on Nurses' performance regarding oxygen administration safety for children with respiratory disorders - Doaa Bahig Anwr Akl; Donia Elsaid Fathi Zaghamir; Mohamed Gamal Elsehrawy; Om Hashim Mahmoud Mahmoud Saadoon; Amal Abd Elhaleem Farahat; Maha Mahmoud Mahmoud Saadoon (Elsevier, 2024)
Background: Supplemental oxygen therapy is one of the main therapies used to manage respiratory distress; it must be given in a way that is both safe and efficient. To provide standardized care, competency-based training should be designed to prioritize the practical skills and talents of the nurses over the provision of theoretical knowledge. The study aimed to evaluate the effectiveness of competency-based training on nurses' performance regarding oxygen administration safety for infants with respiratory disorders. The setting: The study was conducted at the pediatric critical care units at Mansoura University Hospital. Design: The quasi-experimental study was used. The sample: A convenient sampling technique was used for recruiting pediatric critical care nurses and the infants who were admitted in the previous setting. Data collection: three tools were utilized in this study: the first was a structured interview questionnaire encompassing the socio-demographic characteristics of the studied nurses and infants. The second tool is nurses' knowledge and an observation checklist to assess nurse practices regarding oxygen administration safety. The third tool, the nurse competence scale (NCS). Results: pediatric critical care nurses' standardization (knowledge, practice, and knowledge application) through pre- and post-intervention. It showed a marked improvement in mean score and standard deviation in the post compared to pre, and the total mean was in the post (15.9 ± 3.8) compared to pre (33.5 ± 7.2) with a p-value < 0.001. Conclusion: After the implementation of the competency based training program regarding oxygen administration safety.Recommendations.To increase standardization in nursing care practices and produce the best patient outcomes, competency-based training should be applied to all aspects of health care delivery.